دور الإفصاح المحاسبي للقوائم المالية في التشخيص المالي لمؤسسة الرويبة للمشروبات 2012-2015 - قتال, عبد العزيز; يوسفي, رفيق (University of eloued - جامعة الوادي, 2018)
يعتبر الإفصاح المحاسبي في القوائم المالية للمؤسسات الاقتصادية محكوم بعدة محددات بحيث يتم تحديد كمية المعلومات الواجب الإفصاح عنها، وتتمثل هذه المحددات في طبيعة العمل لهذه المؤسسات وما يتطلبه الامر من ضرورة الحفاظ على أسرار لا يجوز الإفصاح عنها هذا من جهة ، ومن جهة أخرى أغلبية المؤسسات الاقتصادية تابعة القطاع العام، فان عملية الإفصاح وتقديم المعلومات تخضع لإشراف السلطات الحكومية، وبالتالي تقتصر الإفصاح الموجود على المعلومات المختصرة، ونلاحظ في الوقت الحاضر ظهور المؤسسات الاقتصادية الخاصة مثل مؤسسة الروبية للمشروبات كمثال للإفصاح عن القوائم المالية لعدة سنوات، يتم من خلالها التشخيص المالي لهذه للمؤسسة ومعرفة المراكز المالية في هذه المؤسسة، ومعرفة المخاطر قبل وقوعها. واستنتاج ان لها القدرة على البقاء والمنافسة في السوق. The accounting disclosure in the financial statements of economic institutions is governed by several parameters so that determine the amount of information to be disclosed, and are these determinants in the nature of the work of these institutions and what it takes from the need to preserve the secrets may not be disclosed on the one hand, and on the other hand, the majority of economic institutions a subsidiary of the public sector, the disclosure and the provision of information is subject to the supervision of government authorities, and therefore the disclosure on the summary information only, and note the time being the emergence of special economic institutions such as the rupee Foundation for drinks as an example for the disclosure of financial statements for several years, by which financial diagnosis for this institution and find out financial centers in this institution, and know the risks before they occur. The conclusion that has the ability to survive and compete in the market
مقال
Keywords: الإفصاح المحاسبي، التقارير المالية، النسب المالية، المؤسسات الاقتصادية Disclosure of accounting, financial reporting, financial ratios, economic institutions